Segurança para a execução: propostas de aperfeiçoamento da penhora de criptoativos nas execuções fiscais - Silveira, Artur Barbosa da (2024)
This thesis, prepared within the scope of the Doctorate in Law program at Universidade Nove de Julho, aims to present proposals for improving the seizure of cryptoactives in the context of tax executions. The thesis is divided into three chapters, the first being conceptual, the second contextualizing the research problem and the third presenting hypotheses based on two fronts of complementary studies. Thus, initially, the emergence of cryptoactives as a disruptive form of capital circulation, their regulatory treatment in Brazil and the world and their legal nature will be explained. Next, we will study tax foreclosures focusing on their procedure and the qualification of cryptoactives as assets subject to seizure. In the final chapter, the first research front will be based on the study of institutional dialogues in public policies to combat structured tax fraud involving cryptoassets, enabling greater tracking, location and seizure of those virtual assets within the scope of tax executions. The second research front will address aspects of improving the cryptoactive seizure mechanism itself, which involve the need to update the judicial technological system - in particular its integration with the blockchain -, better certification of the seizure with the help of title registries and documents and, finally, some specific legislative changes to the Tax Execution Law.